Between idiosyncratic features and market needs - Gutiérrez-Chico, Fernando (Universidad Centro Latinoamericano de Economía Humana (Universidad CLAEH), 2021)
Athletic Bilbao is known in the world of football for its unique player policy. It only recruits footballers who were born and/or raised in one of the seven provinces that comprise the Basque Country. Thus, academy and territory represent the variables of allegiance, which are interdependent and reciprocally regulatory. This policy, of a customary nature, is still in force in an era marked by globalization and commercialization of football. In this context, the article seeks to explore the concepts of local and global built by its fans through the philosophy of the team (policy of the club). The purpose is to know how the local is redefined, interpreted, and how it persists in the current context of football globalization and marketability. To this end, a qualitative approach is mainly used. Ethnographic fieldwork has been chosen. Semi-structured interviews have been conducted in depth with 25 followers of the team, born in Bizkaia and Castilla y León, who reside in the latter autonomous community. It can be concluded that the concept of idiosyncratic features defines the local scene. Conversely, the global one is conceived as aligned with the international commercialization of players.